High-Pressure Pre-Treatment of Kappaphycus alvarezii: Effect of Drying Rate on Physicochemical Properties and Antioxidant Activities - Ahmad Fahmi Lim, Ahmad Fakhzan Lim; Azhani Amran, Siti; Zulkurnain, Musfirah; Majahar Ali, Majid Khan; Azima, Fauzan; Wan Ishak, Wan Rosli (Jurnal Gizi dan Pangan, 2025)
This study focuses on High-Pressure Pre-Treatment to enhance the seaweed's nutritional value and antioxidant potential, which is highly relevant and aligns with the demand for improved food processing techniques that preserve bioactive compounds. High-Pressure Processing (HPP) was applied at varying levels (0, 200, 400, and 600 MPa) to assess its impact on drying efficiency, physicochemical properties, and antioxidant activities. High-Pressure Processing (HPP) at 200 MPa, 400 MPa, and 600 MPa enhanced the drying performance and antioxidant properties of Kappaphycus alvarezii. The 600 MPa treatment achieved the fastest drying rate and the highest antioxidant capacity, thereby enhancing the seaweed’s functional properties. Moreover, the 600 MPa treatment yielded the highest total phenolic content (50.68±1.51 mg GAE/100 g) and a significant enhancement in total flavonoid content (5.54±0.29 mg QE/100 g). These compounds are crucial for neutralizing free radicals and mitigating oxidative stress. Furthermore, the 600 MPa treatment demonstrated a significant increase in ferric reducing antioxidant power assay (44.58±2.56 mg FeSO4/100 g) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (18.86±0.66%) relative to the untreated sample, highlighting the improved antioxidant potential associated with high-pressure treatment. These findings indicate that HPP not only preserves but also enhances the antioxidant properties of Kappaphycus alvarezii, which are vital for its health benefits. Additionally, color analysis revealed significant changes in the lightness and chromaticity of the seaweed post-treatment, suggesting improvements in its visual appeal. This research underscores the capability of HPP technology to improve the drying efficiency of Kappaphycus alvarezii, thereby boosting its antioxidative properties, marketability, and versatility in various applications.